An analysis of leitmotifs in Batman vs Superman / Khairul Aziem Ahmad Rashidi - Ahmad Rashidi, Khairul Aziem (Faculty of Music, 2017)
What is film music? According to Madsen (2010),"Film music is defined as any piece of original music composed specifically for use in a Hollywood-produced motion picture. This music can come in a variety of styles, ranging from a traditional symphony orchestra to a jazz or rock approach" (p. 3). Film music is related to film scoring. According to Brown (2016), film scoring is the process of composing original music for the specific purpose of film accompaniment. [Film music] is characterized by its power to define meaning and to express emotion: film music guides our response to the images and connects us to them (Kalinak, nd.). A musical score can comment on visual information and dialogue by reinforcing or undercutting that information; it can provide spatial, thematic, or temporal transitions; it can helps and accompanying on situation and character; it can direct attention to key information on the screen; it can counterpoint or underscore a visual impression (Kalinak, 1982, p. 2). Besides that, according to Leach (2010) film scoring is craft and art or writing music in sync to visuals.